PREDICTORS OF EMOTIONAL INTELLIGENCE AMONG DIFFERENT CULTURE: SYSTEMATIC REVIEW AND META-ANALYSIS - Azadeh Mousavi (Study Program Guidance and Counseling, Univesitas Pendidik, 2021)
Psychologists are encouraged to find the most significant predictors of emotional regulation among different cultures to improve mental health and wellbeing. In this regards the systematic review was conducted on original published articles using ‘religiosity ‘critical thinking’ ‘thinking style’ and ‘emotional intelligence’ as keywords which were collected from Google Scholar, Science Direct, Web of Science, and PubMed by (Mendeley Reference Manager) for relevant articles written in English. Also, a manual search of Iranian articles in the Persian databases, such as Noormags, was carried out.All articles were searched from 1997 till 2021. Among the 21 articles in the review of religiosity, 20 critical thinking and 13 thinking style, with the separate identifying role of each variable in regulating emotion that gathered according to the inclusion and exclusion criteria of SIGN checklist and analyzed by Comprehensive Meta-Analysis software version 3 (CMA 3) critical thinking showed the highest correlation with emotional regulation (critical thinking r = 0.365) (religiosity r=0.310) (critical thinking r = 0.365) (thinking style r = 0.324). Therefore, training the ways of thinking critically is a pathway to catch emotional wellbeing.